Spotreba léciv v seniorské populaci a rizika polyfarmakoterapie ve stárí - Kubesová, H; Holík, J; Weber, P; Polcarová, V; Matejovský, J; Mazalová, K; Slapák, J (Casopis lekaru ceskych, 2006)
BACKGROUND: One of our previous studies was aimed at the consumption of prescribed drugs by the elderly population. The average per day number of drugs was 4.6 (maximum 13). Existence of freely obtainable drugs with massive advertisements brings a question, how many of those drugs it is necessary to add in order to estimate probability of interaction and undesirable drug effects. In order to achieve valid information, students of the sixth year of General medicine program during their practical course at general practitioners were asked to interview randomly selected senior patients. They asked on the number, type, and price of freely obtainable drugs which they use. Data were evaluated from interviews accomplished during academic years 2001/2002 and 2004/2005. METHODS AND RESULTS: Our cohort included 252 men and 148 women with average age of 78.7 years. Average number of freely obtainable drugs was 2.26 at the beginning and 2.32 at the end of study. Only 34% of questioned did not buy any of those drugs at all or only exceptionally, 66% reported buying once a month or weekly. 44% of seniors buy analgetics, 58% buy vitamins, 37% food supplements, 36% non steroid antirheumatics, 46% cold prevention drugs, 30% anti-constipation drugs. Contrary to our expectation, positive correlation between the sums given for the personal participation on the drug costs and that given for freely obtainable drugs was found. It is not possible to expect, that polymorbidic patient with several prescribed drugs would buy less of freely obtainable drugs even due to the financial requirements. CONCLUSIONS: Freely obtainable drugs, many of them composites, can represent significant source of interactions and undesirable drug effects. They can also significantly modulate compliance of the senior. The high percentage of seniors buying freely obtainable drugs requires aimed questions on the pharmacological history.
Keywords: léky bez předpisu; Česká republika; polypharmacy; Drug Utilization; lidé; Female; senioři; lékové předpisy; mužské pohlaví; Male; spotřeba léčiv; Aged; Czech Republic; Nonprescription Drugs; Polypharmacy; ženské pohlaví; Drug Prescriptions; Humans